Synovial Sarcoma of the Larynx: Report of a Case and Review of Literature - Geetha Narayanan; Anto Baby; Thara Somanathan; Sreedevi Konoth (Case Reports in Otolaryngology)
Sarcomas account for less than 1% of malignant neoplasms arising in the head and neck in adults. Laryngeal synovial sarcoma is an extremely rare form of laryngeal malignancy with less than 20 cases reported in the literature. We report the case of a 48-year-old man with synovial sarcoma of the larynx. He underwent excision of the tumor followed by radiation. He is alive in remission at 36 months. The literature on synovial sarcoma of the larynx is reviewed.